2009
DOI: 10.1253/circj.cj-08-0905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cilostazol Treatment on Adiponectin and Soluble CD40 Ligand Levels in Diabetic Patients With Peripheral Arterial Occlusion Disease

Abstract: Circ J 2009; 73: 948 -954 eripheral arterial occlusion disease (PAOD) is a common manifestation of atherosclerosis in patients with type 2 diabetes mellitus (DM). 1,2 In Taiwan, approximately 33-50% of patients undergoing lower extremity amputation have DM, and more than 50% of them have PAOD. 3,4 The risk factors associated with PAOD are similar to those for coronary artery disease and cerebrovascular disease.It has been proved that atherosclerosis-related macroangiopathy is a result of chronic inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…30 Moreover, a recent study suggested that prostaglandin E1 in lipid microspheres improved walking ability and the quality of life as self-evaluated by patients with PVD. 31 In addition, supervised exercise training improved cardiovascular mortality and morbidity in patients with PVD, which suggests that exercise training should be considered as a secondary prevention strategy for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, a recent study suggested that prostaglandin E1 in lipid microspheres improved walking ability and the quality of life as self-evaluated by patients with PVD. 31 In addition, supervised exercise training improved cardiovascular mortality and morbidity in patients with PVD, which suggests that exercise training should be considered as a secondary prevention strategy for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, agents that increase circulating adiponectin levels could represent a potential therapeutic target for the prevention of ischemic stroke. Probucol can significantly elevate serum adiponectin concentrations in diabetic rats (Zhang et al, 2009), and cilostazol increases adiponectin levels in type 2 diabetic patients and in a diabetic animal model (Hsieh and Wang, 2009). In the present study, the accumulation of adiponectin with eNOS in the vasculature in the combinatorial therapy group may have served to protect the vasculature.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Moreover, the consequence of diabetics with PAOD could be ameliorated by taking cilostazol to reduce high sensitivity C-reactive protein levels and the soluble form of the CD40 ligand and to elevate the level of adiponectin, hence hindering the atherogenesis and chronic inflammation progression [46]. Furthermore, a current study declared that prostaglandin E1 in lipid microspheres enhanced walking ability and Life quality as self-estimated by PAOD patients [47].…”
Section: Discussionmentioning
confidence: 76%